Effect of various type of shear walls on behavior of tall building due to seismic force - Syamsir A.; Allah A.K.; Naganathan S.; Zainoodin M.; Nor N.M.; Beddu S. (American Institute of Physics Inc., 2023)
This paper presents the investigation of shear walls behavior in seismic response of tall buildings. In this study, shear wall system was tested for one building with total ten systems namely I, II, III, IV, V, VI, VII, VIII, IX, and X. Seismic loads were applied to the building models using response spectrum method. In the response spectrum data, the acceleration equals the ground acceleration 1.0 g on its direction and 0.3g in the opposite direction. The result indicated, the comparison of all model in term of displacement show model VI produced the lowest lateral displacement and base shear load of 5.8 mm and 2407 kN, respectively, while model II has the highest displacement of 11.57 mm. The study show, displacement of model VI was decreased up to 21% by adding boundary elements compared to model I which both of the model located at the same location. Thus, it can be concluded that, in term of displacement the optimum solution to resist seismic load by provide a shear wall with boundary elements near the core of the building as applied to Model VI. 2021 American Institute of Physics Inc.. All rights reserved.